2022
DOI: 10.1007/s15010-022-01942-4
|View full text |Cite
|
Sign up to set email alerts
|

Work performance among healthcare workers with post COVID-19 syndrome and its relation to antibody response

Abstract: Purpose Health care workers (HCWs) are frontliners in facing Cornoravirus disease (COVID-19) and hence are amongst the high risk groups of acquiring COVID-19 infection. The impact of COVID-19 infection and post-infection sequelae on work performance has deleterious effects on HCWs and the whole community. The aim of the current study is to assess the impact of COVID-19 infection particularly those with post-COVID-19 syndrome on work performance among HCWs and to determine if a possible relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Han et al [ 84 ] and Mazza et al [ 85 ] confirm the current finding that COVID-19 survivors continue to experience post-COVID symptoms, such as fatigue, depression, and anxiety, even after one year. D’Ettorre et al [ 10 ] showed an incidence between 16 and 87% for post-COVID in working-age patients, and up to 70% for healthcare workers [ 16 , 53 , 86 ]. The systematic review by Soril and colleagues [ 87 ] confirmed that psychological post-COVID symptoms (dyspnea, fatigue, anxiety, and depression) improved after several pulmonary rehabilitation programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al [ 84 ] and Mazza et al [ 85 ] confirm the current finding that COVID-19 survivors continue to experience post-COVID symptoms, such as fatigue, depression, and anxiety, even after one year. D’Ettorre et al [ 10 ] showed an incidence between 16 and 87% for post-COVID in working-age patients, and up to 70% for healthcare workers [ 16 , 53 , 86 ]. The systematic review by Soril and colleagues [ 87 ] confirmed that psychological post-COVID symptoms (dyspnea, fatigue, anxiety, and depression) improved after several pulmonary rehabilitation programs.…”
Section: Discussionmentioning
confidence: 99%
“…Comparable prevalence rates were found up to six months after acute infection [ 17 , 50 , 51 ]. Among healthcare workers, depression and anxiety have a prevalence of 8–44% three to ten months after acute COVID-19 [ 15 , 52 , 53 ]. Results regarding the risk factors for higher rates of anxiety and depression are inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, there was no standardized presentation of absenteeism data across studies; therefore, a meta-analysis was not considered feasible. Another possible limitation is that information about COVID-19 vaccination refusal, burnout, mental health illness, or post-COVID-19 syndrome as a cause of HCP absenteeism is not clearly mentioned in all reviewed studies, despite their increased prevalence among HCP during the COVID-19 pandemic compared with the pre-pandemic period [60][61][62][63]. Lastly, the impact of school closures on healthcare workforce because of child-care obligations was not considered [64].…”
Section: Limitationsmentioning
confidence: 99%
“…healthcare workers, teachers) who contract the disease [8]. The substantial impact of LC on productivity has likewise been confirmed by numerous UK and non-UK studies of general or general working populations [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] and specific professions including healthcare workers, teachers, and athletes [29][30][31][32][33]. Productivity in employment not only increases national income, but is also a determinant of health and well-being [34,35].…”
mentioning
confidence: 97%